The Visibility of Open Access Monographs in a European Context: Full Report - Montgomery, Lucy; Neylon, C.; Ozaygen, A.; Saunders, N.; Pinter, F. (OPERAS-D, 2018)
This report explores the extent to which Open Access (OA) specialist scholarly books can be seen by the communities that might make use of them. It also identifies the key challenges that will need to be tackled in order to ensure that OA books are fully integrated into digital landscapes of scholarship; as well as the steps that need to be taken to achieve this goal. The report focuses on Open Access books made available by publishers and platforms that are part of the OPERAS network, which is focused on the development of European research infrastructure for the development of open scholarly communication. Specialist scholarly books are the core research output of the Humanities and Social Sciences. Ensuring that they are integrated into digital landscapes of scholarship will play a decisive role in the future of these disciplines, and their impact on the world. Identifying gaps in existing infrastructure and creating a roadmap to address them is vital groundwork. This report forms part of the OPERAS-D project, which focuses on the development of a European e-infrastructure for open access publications in the Humanities and Social Sciences. Knowledge Unlatched Research is a core partner in the OPERAS-D project. KU Research is an independent research and analysis group focusing on strategy and analytics that support the ecosystem of scholarly monographs.